DECONSTRUCTION OF THE DISCOURSE OF FEMININITY: A CASE OF THAI GIRLS’ SCHOOLS - Satienchayakorn, Natakorn; Jimarkon, Pattamawan (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
The study investigates the construction of femininity ideologies of girls-only school websites in Thailand and deconstructs them for analysis at the lexical level. Ideological beliefs underlying the custom of upbringing of young women in Thai cultural contexts are the focus of investigation. We pay a particular attention to how the schools communicate their key messages of vision, mission, core values, and about us on their websites and conduct a corpus-driven discourse analysis on the data. Findings from running tests of frequency and collocation reveal the traits of femininity constructed in the discourse, built the praising of obedience, submissiveness and lady-like features. We conclude that benevolent sexism is a common cultural practice evident in educational institutions.